2004
DOI: 10.1128/jb.186.21.7161-7174.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Completely Sequenced Plasmid pEST4011 Contains a Novel IncP1 Backbone and a Catabolic Transposon Harboring tfd Genes for 2,4-Dichlorophenoxyacetic Acid Degradation

Abstract: The herbicide 2,4-dichlorophenoxyacetic acid (2,4-D)-degrading bacterium Achromobacter xylosoxidans subsp. denitrificans strain EST4002 contains plasmid pEST4011. This plasmid ensures its host a stable 2,4-D ؉ phenotype. We determined the complete 76,958-bp nucleotide sequence of pEST4011. This plasmid is a deletion and duplication derivative of pD2M4, the 95-kb highly unstable laboratory ancestor of pEST4011, and was self-generated during different laboratory manipulations performed to increase the stability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
86
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 56 publications
(45 reference statements)
4
86
0
Order By: Relevance
“…Some of the chlorocatechol gene clusters have been found to be carried on transposons (30,40,45,63) or a phage-like element (49,55). Recent reports on the entire sequencing of two 2,4-D degradative plasmids, pJP4 and pEST4011, illustrated their genetic features of basic plasmid functions such as replication, maintenance, and transfer, shared with other broad-host-range IncP1 plasmids (59,63). These findings have revealed some of the reasons underlying the wide distribution of the gene clusters of the chlorocatechol ortho-cleavage pathway.…”
mentioning
confidence: 99%
“…Some of the chlorocatechol gene clusters have been found to be carried on transposons (30,40,45,63) or a phage-like element (49,55). Recent reports on the entire sequencing of two 2,4-D degradative plasmids, pJP4 and pEST4011, illustrated their genetic features of basic plasmid functions such as replication, maintenance, and transfer, shared with other broad-host-range IncP1 plasmids (59,63). These findings have revealed some of the reasons underlying the wide distribution of the gene clusters of the chlorocatechol ortho-cleavage pathway.…”
mentioning
confidence: 99%
“…The transfer of these plasmids occurs not only among the Proteobacteria, but also between bacteria of other phyla (1). Note that many degradative plasmids belong to the IncP-1 group, and that the nucleotide sequences of many such plasmids have been determined, e.g., pA81, pADP-1, pJP4, pEST4011, and pUO1 (46,57,100,114,121). The core regions of IncP-1 group plasmids show high identity.…”
Section: Behavior Of Degradative Plasmids In Environmentsmentioning
confidence: 99%
“…Such transfer events across taxa, and subsequent mutations and rearrangements of the catabolic genes, have contributed to the rapid adaptation of bacteria to novel chemical compounds (46,52). Recent studies have shown that genes for the degradation of xenobiotic compounds, such as atrazine (31), haloacetate (44), and 2,4-dichlorophenoxyacetate (58), are predominantly carried on the incompatibility group P-1 (IncP-1) plasmids, whereas genes that encode the degradation of natural aromatic hydrocarbons, such as phenol (41), naphthalene (10,28), and toluene/xylenes (18), are usually found on IncP-2, IncP-7, and IncP-9 plasmids (9,51). Large catabolic gene clusters are also found on mobile elements integrated into bacterial chromosomes as genomic islands or conjugative transposons (8,14,53,56).…”
mentioning
confidence: 99%